Prison Of Poverty For Traditional Fishers - Seger Sugiyanto; Pawennari Hijjang; Ashaluddin Jalil (Neo Journal of economy and social humanities, 2022)
This paper was a research of the traditional fishers’ life and the poverty prison of the Natural Resources in Teluk Belitung Village, Merbau District. The researchers described the current situation of traditional fishers' households and their value orientation towards jobs as fishers with a bargaining position. The mix method was chosen as the approaching model to understand the subject matter with the data analysis phase, including categorizing, compiling labels, and concluding. The monopoly of the fisheries economy by some Chinese entrepreneurs has maintained poverty for traditional fishers who worked for them or not. Debt guarantees were ways to cover up detrimental situations and destroy fishery resources in the research area. The researchers used the Kluckhohn approach to uncover the actual value orientation of fishers in a tight situation. Fishers understood that using dencis threatened the environment, but this method was chosen to maintain their position as fishers with sufficient income. There were other alternative jobs such as gardening. However, when they did it, they required seeds, fertilizers, and other types of equipment. The poor economic conditions made it challenging to do gardening while the guarantee of life for their households was lacking, especially from the local government.